PENGEMBANGAN VIDEO ANIMASI PEMERIKSAAN GULA DARAH PUASA (VAP-GDP) SEBAGAI PENCEGAHAN DIABETES MELITUS REMAJA POSBINDU LILY - Risti Sulistiawati; Ridwan Setiawan (Jurnal Kesehatan Siliwangi, 2025)
Background: Diabetes Mellitus (DM) is a chronic disease caused by impaired insulin production or function. In West Java, the number of DM cases among individuals aged ≥15 years has reached 570,611. This situation is concerning, as reports from the Cimahi City Health Office indicate a 20% increase in adolescent DM cases over the past two years. This highlights the importance of early prevention and education, one of which is through animated video-based education. Objective: This study aims to develop an animated video on fasting blood glucose testing (VAP-GDP) as an effort to prevent Diabetes Mellitus among adolescents at Posbindu Lily using the ADDIE model. Methods: This research employs a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The sample consisted of 40 adolescents selected through total sampling technique. The research was conducted at Posbindu Lily. Data collection used questionnaires that had been tested for validity and reliability. Data analysis was performed using univariate and bivariate methods with the Wilcoxon test. Results: The 6-minute 24-second animated video was validated by material experts (94.4%) with a "Very Good" rating and media experts (91.7%) with a "Highly Suitable" rating. The Wilcoxon test results showed a significant increase in knowledge (p < 0.05) after the intervention. Conclusion: The VAP-GDP animated video was deemed highly suitable and effective in increasing adolescents' knowledge about the importance of fasting blood glucose testing as a preventive measure against DM